2021
DOI: 10.3389/fmolb.2021.790304
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ATP Levels Determine the Stability of a Nucleotide Kinase

Abstract: The energy currency of the cell ATP, is used by kinases to drive key cellular processes. However, the connection of cellular ATP abundance and protein stability is still under investigation. Using Fast Relaxation Imaging paired with alanine scanning and ATP depletion experiments, we study the nucleotide kinase (APSK) domain of 3′-phosphoadenosine-5′-phosphosulfate (PAPS) synthase, a marginally stable protein. Here, we show that the in-cell stability of the APSK is determined by ligand binding and directly conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Missense mutations in nuclear deubiquitinase BAP1 were previously shown to induce destabilization and aggregation of this enzyme, with the latter being suggested as the main cause of its functional loss (Bhattacharya et al, 2016). In fact, this hypothesis is further supported by our previous studies (Brylski et al, 2021) using an alanine scanning mutagenesis of the substrate binding site of APSK37 in HeLa cells. The results revealed a large range of different in-cell stabilities for the single point mutations (ΔG f 0 = −10.7 to +13.8 kJ/mol).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Missense mutations in nuclear deubiquitinase BAP1 were previously shown to induce destabilization and aggregation of this enzyme, with the latter being suggested as the main cause of its functional loss (Bhattacharya et al, 2016). In fact, this hypothesis is further supported by our previous studies (Brylski et al, 2021) using an alanine scanning mutagenesis of the substrate binding site of APSK37 in HeLa cells. The results revealed a large range of different in-cell stabilities for the single point mutations (ΔG f 0 = −10.7 to +13.8 kJ/mol).…”
Section: Discussionsupporting
confidence: 53%
“…We analyzed the effect of disease-related mutations on the folding stability and aggregation of the APS kinase domain of the bifunctional PAPSS2 protein, using our recently established APSK folding sensor (APSK37) (Brylski et al, 2021). The sensor reports intramolecular FRET between the N-terminal AcGFP1 and the C-terminal mCherry fusion proteins (see Materials and Methods for details).…”
Section: Mutations In Apsk37 Reveal Distinct Folding Stabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of ATP acting as a cosolute to maintain biomolecular processes in cells could explain why the cellular ATP concentration (5–10 mM) exceeds the level required to sustain energy-consuming processes by a factor of up to 1000. ,,, In line with this hypothesis, previous studies showed that elevated ATP levels could increase protein solubility and maintain the liquid-like properties of nucleoli, stress granules, , and, in general, the cytoplasm of eukaryotes and prokaryotes. ,,,, …”
Section: Discussionmentioning
confidence: 89%
“…To probe whether changes in the ATP concentration also affect the folding stability of (CAG) 20 and lm4U* in cells, we conducted ATP depletion experiments, adding final concentrations of 1 mM KCN and 10 mM 2-deoxyglucose to the medium . ATP depletion was monitored by the ATeam ATP concentration sensor (see Figure S9 and Supporting Information Materials and Methods for further details), , and (CAG) 20 RNA folding stability was assessed at the minimum ATP level. The normalized FRET ratio decreased from 1.0 to 0.6, corresponding to a decrease in the cellular ATP concentration by 2–3 mM .…”
Section: Resultsmentioning
confidence: 99%